Implementing SEL Programs to Enhance Academic and Socio-Emotional Competencies in Elementary Schools: A Systematic Literature Review - Sri Mellia Marinda; Muhamad Adhi Maretnas Harapan; Widodo Widodo; Marsambas Marsambas; Muhammad Nurfazri (UIN Sunan Gunung Djati Bandung, 2025)
Social and Emotional Learning (SEL) is an increasingly important educational approach to support students' social, emotional, and academic development. This study aims to explore various approaches and strategies for implementing SEL in elementary schools and to identify their impact on students' academic achievement and social-emotional skills development. The method used was a systematic literature review (SLR) based on the PRISMA guidelines. Articles were obtained from leading academic databases such as ScienceDirect, ERIC, and DOAJ, with a publication coverage between January 2021 and March 2025. Of the 250 articles identified, 13 met the selection criteria and were further analyzed. The results of the study indicate that the implementation of SEL, both through classroom-based approaches and whole-school approaches, has a significant positive impact on improving academic achievement and the development of students' social-emotional skills, such as self-awareness, emotional management, and social interaction skills. The program's success is greatly influenced by supportive school leadership, active teacher involvement, and the use of learning media sensitive to cultural contexts. The practical implications of these findings suggest the importance of integrating SEL into the elementary school curriculum and the need for ongoing training for teachers and policy support from education stakeholders to create holistic and inclusive learning environments.